2017
DOI: 10.1017/s0956536116000390
|View full text |Cite
|
Sign up to set email alerts
|

A Social Network Analysis of the Postclassic Lowland Maya Obsidian Projectile Industry

Abstract: This study addresses the role of prehistoric ethnopolitical divisions, factionalism, and alliances in macroregional economic models. The Mesoamerican Late Postclassic period (a.d. 1350–1525) is characterized by its “cosmopolitan” economy featuring long distance exchange of raw materials and finished products. Such characterizations are examined through a provenance analysis of small obsidian projectile points from the Maya lowlands of Guatemala, Mexico, Belize, and Honduras. Obsidian artifacts are analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 55 publications
(98 reference statements)
0
11
0
Order By: Relevance
“…Volcanic origins of obsidian used for small projectile points also varied significantly across the subregion. SNA from a previously published study (Meissner 2017:148–149) revealed a strong subnetwork of obsidian exchange among centers in Belize involving Ixtepeque obsidian (Figure 6). In contrast, the Late Postclassic Peten Lakes region had more diversified patterns of procurement that included El Chayal and San Martin Jilotepeque in addition to Ixtepeque.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…Volcanic origins of obsidian used for small projectile points also varied significantly across the subregion. SNA from a previously published study (Meissner 2017:148–149) revealed a strong subnetwork of obsidian exchange among centers in Belize involving Ixtepeque obsidian (Figure 6). In contrast, the Late Postclassic Peten Lakes region had more diversified patterns of procurement that included El Chayal and San Martin Jilotepeque in addition to Ixtepeque.…”
Section: Resultsmentioning
confidence: 76%
“…Obsidian points were subclassified by volcanic source and reported here from a previous study that used both instrumental portable x-ray fluorescence and visual analysis (Braswell et al 2000; Meissner 2017). The resulting data were compared graphically using social network analysis (SNA) to better understand raw material preferences throughout the subregion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of all the structures excavated at the site, Structure 719 yielded more obsidian prismatic blade segments ( n = 303) than any other, and also the highest frequencies of projectile points per excavated square meter in comparison to other civic-ceremonial structures (0.08/m 2 ; n = 44; Meissner 2014:413, Figure 7.29). X-ray fluorescence (XRF) analyses (Rice and Cecil 2009; Meissner 2017 used pXRF) revealed that 90 percent of the more than 300 analyzed obsidian artifacts throughout the site came from varied Guatemalan source flows (Table 4). The chert and other siliceous stone points were assumed to be made of local materials, although one point recovered from a bench seat was made of honey-brown chert from the Northern Belize Chert Bearing Zone.…”
Section: Lithic Artifactsmentioning
confidence: 99%